2021
DOI: 10.1111/mpp.13051
|View full text |Cite
|
Sign up to set email alerts
|

A Cas12a‐based gene editing system for Phytophthora infestans reveals monoallelic expression of an elicitor

Abstract: Tools for functional genomics are critical for understanding the biology of plant pathogens. This is especially true for the oomycete genus Phytophthora, which causes numerous devastating crop diseases. The infamous pathogen Phytophthora infestans, for example, is a limiting factor in potato production and can destroy fields in little more than a week (Leesutthiphonchai et al., 2018). Studies of P. infestans have shed light on oomycete metabolism, spore biology, and pathogenesis, thus helping to advance strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 83 publications
(121 reference statements)
0
22
0
Order By: Relevance
“…The application of CRISPR/Cas has addressed many of the previous obstacles for editing oomycete genes, and successful transformants have been generated, such as from the use of a CRISPR/Cas12a system in P. infestans, which has enabled a greater capability for gene editing in oomycetes generally [64]. Similarly, point mutations introduced into P. sojae [65] using CRISPR/Cas9 conferred resistance to the fungicide oxathiapiprolin.…”
Section: Gene Editing Using Crispr/casmentioning
confidence: 99%
“…The application of CRISPR/Cas has addressed many of the previous obstacles for editing oomycete genes, and successful transformants have been generated, such as from the use of a CRISPR/Cas12a system in P. infestans, which has enabled a greater capability for gene editing in oomycetes generally [64]. Similarly, point mutations introduced into P. sojae [65] using CRISPR/Cas9 conferred resistance to the fungicide oxathiapiprolin.…”
Section: Gene Editing Using Crispr/casmentioning
confidence: 99%
“…Meanwhile, some studies have shown that the off-target effect is extremely low in iPSCs [44,45]. Compared with Cas9, Cas12a is more sensitive to mismatches in the guide RNA and has lower off-target effects [46]. In this study, no off-target cleavage was observed at the seven putative sites, even when the COE expression lasted 75 days.…”
Section: Discussionmentioning
confidence: 51%
“…In P. infestans , however, CRISPR-Cas9-mediated gene editing was not successful ( van den Hoogen and Govers, 2018b ). A recent study by Ah-Fong et al (2021) showed that Cas9 is toxic for this species, but with Cas12a as nuclease they obtained transformants that are viable and have small deletions in the target gene, the inf1 elicitin gene. This is another major leap forward as it demonstrates the successful implementation of a promising gene editing tool in P. infestans .…”
Section: The Interplay Between Host and Oomycete Pathogensmentioning
confidence: 99%